Antioxidant capacity in fruits of different pineapple genotypes (Annona squamosa L. x Annona Cherimola) / Capacidade antioxidante em frutos de diferentes genótipos de pinheira (Annona squamosa L. x Annona Cherimola) - José Dailson Silva de Oliveira; Maria Gleysiane Souza dos Santos; Jean Tiago Correia Lima; Walter Soares Costa Filho; Kelly Cristina Barbosa Silva Santos; João Gomes da Costa (Universidade Estadual de Alagoas, 2019)
Food contains nutrients that are essential for the defense mechanisms of cells against free radicals. Various fruits and vegetables are able to fight these free radicals, thus being natural antioxidants. The objective of this work was to evaluate the antioxidant capacity of the fruits of the different genotypes of pinheira and a hybrid of atemoieira, from the genetic improvement program of Embrapa Tabuleiros Corteiros/Research Execution Unit of Rio Largo, with the purpose of contributing to the selection of promising genotypes and to obtain value-added genetic material. Mature samples of fruits of the species Anonna Squamosa L. and Annona Atemóya were collected in the municipality of Palmeira dos Índios, Alagoas, to investigate their ability to sequester the free radical 2,2-diphenyl-1- picrylhydrazyl (DPPH) and its capacity inhibit oxidation. To obtain the extracts, the pulp was separated from the samples and transferred to erlenmeyers, where each sample received a volume of 350 mL of ethanol. After 72 hours the supernatant was collected and an additional 350 mL of ethanol was added to the remaining material. This process was repeated three times. The supernatant was collected, filtered and evaporated by means of a rotavaporator, at the end of which the crude extract was obtained. Atemóia presented 92.42% antioxidant activity at a concentration of 2,5 mg/mL, while one extract of a pineapple sample presented 98.62% antioxidant activity, at a concentration of 5,0 mg/mL. These results show that genetic gains can be obtained through simple improvement methods.